The Effect of Machine Learning-Assisted Inquiry Based Learning Size Model on Students' Problem-Solving Thinking Skills - Sapulete, Heppy; Tomi Apra santosa; Hasyim Mahmud Wantu; Ahamd Zain Sarnoto; Aat Ruchiat Nungraha; Eko Nursalim; Togam E Panggabean; Alek Irawan Triantho (Asosiasi Ide Bahasa Kepri, 2024)
This study aims to determine the influence of the Machine Learning-assisted Inquiry Based Learning Model on Students' Problem-Solving Thinking Ability. This type of research is a quantitative research with a meta-analysis approach. The data sources in this study come from 12 reputable national and international journals published in 2022-2024. The data collection technique is direct observation through the jury database. The search for data sources in this study is based on google scholar; ERIC, Wiley and Sciencedirect. Data analysis is quantitative data analysis by calculating the effect size value. The results of the study concluded that the inquiry-based learning model assisted by machine learning had a positive influence on students' problem-solving ability with an effect size value of 1,02 in the high effects size category